Clinical and Diagnostical Values of Plasma α-Synuclein and Melatonin Levels in Early Stages of Parkinson’s Disease - Biriuk, V.; Demchenko, A. V.; Gorbachova, S.; Горбачова, Світлана Василівна (My University, 2020)
Parkinson’s disease (PD) is a widespread, progressive neurodegenerative disorder with complex pathogenesis. The combination of its motor and non-motor symptoms significantly impairs a patient’s life quality. The question of targeted patogenetic therapy of Parkinson’s disease is still relevant, which is why biomarkers for early diagnosis and neuroprotective therapy are urgently required.
Keywords: Parkinson’s disease; early stages; α-synuclein; melatonin; cognitive impairment; sleep disorders